KPI tree - a hierarchical relationship structure of key performance indicators for value streams - Bumba Alberto; Gomes Manuel; Jesus Cristiano; Lima Rui M. (Production Engineering Archives, 2023)
Performance Measurement Systems (PMS) have been a potential answer to problems related to production systems monitoring, allowing the management and manipulation of data collected at various levels in organizations. PMS can be defined as a group of indicators in an information system. There are several types of PMS, however, the relationship between indicators in a PMS is still an issue that needs to be explored, as the KPIs in a production system are not independent and may have an intrinsic relationship. The purpose of this paper is to present a multilevel structure and its intrinsic structural relation for managing and analysing KPIs for a value stream production system. This hierarchical structure has different KPI levels such as Improvement KPIs, Monitoring KPIs, and Results KPIs or KPR (Key Performance Results), intrinsically related from the strategic levels to the operational levels. This provides a useful tool for the management of production systems, being used to analyse, and support the organization's continuous improvement processes.